Analysis of methods of design of the flexible systems of productions - L.Ya. Soroka , Lyubomyr (Forestry, Forest, Paper and Woodworking Industry, 2007)
The analysis of methods of design of the flexible systems of productions, their disadvantages, advantages and practical applications, are conducted.